Introduction to the Bible - Hayes, Christine Elizabeth (The open Yale courses series., 2012)
"This book examines the small library of 24 books common to all Jewish and Christian Bibles--books that preserve the efforts of diverse writers over a span of many centuries to make sense of their personal experiences and those of their people, the ancient Israelites. Professor Christine Hayes guides her readers through the complexities of this polyphonous literature that has served as a foundational pillar of Western civilization, underscoring the variety and even disparities among the voices that speak in the biblical texts. Biblical authors wrote in many contexts and responded to a sweeping range of crises and questions concerning issues that were political, economic, historical, cultural, philosophical, religious, and moral. In probing chapters devoted to each of the 24 books of the Hebrew Bible, or Old Testament, Hayes reconstructs the meanings and messages of each book and encourages a deeper appreciation of the historical and cultural settings of ancient biblical literature"--